Cidadania na constituinte e constituição do Brasil : discurso, símbolo, utopia - Santos, Hermano de Oliveira (2018)
When addressing the issue of the legal form of citizenship in Brazil, one must question how the needs and interests of citizens were considered and debated in the Constituent of 1987/1988 and are recognized and protected by the State from the Constitution of 1988. In order to describe the constitutionalisation of citizenship, we seek to explore and explain how relations between citizens and the State are established. It starts from the hypothesis that the rights and duties of citizenship reflect and are used to justify relations of domination, whose effects are varying degrees of inclusion or exclusion, access and exercise of powers by citizens, with intermediation of the State. Adopting as a methodology a multidisciplinary investigation, it is based on the theoretical referential of the genealogy of power procedure, through the application of instruments of critical analysis of textually oriented discourse, on primary and secondary sources of empirical and theoretical bibliographic material, in a qualitative way. This return to the constituent context is justified as a means to achieve the purpose of understanding the the foundations and manifestations in the constitutional text, as its limitations and possibilities in social reality. In a structure divided into three chapters, the following contente are displayed: (1) formation and constituent works used the yearning for popular participation, to establish a constitutional system of democracy based on representation, being citizenship more configured by the State than built by the citizens; (2) oligarchic groups manipulated and manipulate the constituent power using the common needs to meet hegemonic interests, which makes that power a symbolic power and citizens less subject than objects of power, being citizenship subject to regulation and control by the State; and (3) this lack of constituent legitimacy hampers constitutional effectiveness, since power is exercised and justified by agents of the State even without authority being conferred on them by the citizens, which is not criticized as it could by constitutionalist doctrine, making citizenship more utopia than reality.